Microbes, Histology, Blood Analysis, Enterotoxins, and Cytokines: Findings From the ASERF Systemic Symptoms in Women–Biospecimen Analysis Study: Part 3. (18th August 2022) - McGuire, Patricia; Glicksman, Caroline; Wixtrom, Roger; Sung, C James; Hamilton, Robert; Lawrence, Marisa; Haws, Melinda; Ferenz, Sarah; Kadin, Marshall
Abstract: Background: There has been an increasing need to acquire rigorous scientific data to answer the concerns of physicians, patients, and the FDA regarding the self-reported illness identified as breast implant illness (BII). There are no diagnostic tests or specific laboratory values to explain the reported systemic symptoms described by these patients. Objectives: The aim of this study was to determine if there are quantifiable laboratory findings that can be identified in blood, capsule tissue pathology, or microbes that differentiate women with systemic symptoms they attribute to their implants from 2 control groups. Methods: A prospective blinded study enrolled 150 subjects into 3 cohorts: (A) women with systemic symptoms they attribute to implants who requested implant removal; (B) women with breast implants requesting removal or exchange who did not have symptoms attributed to implants; and (C) women undergoing cosmetic mastopexy who have never had any implanted medical device. Capsule tissue underwent detailed analysis and blood was sent from all 3 cohorts to evaluate for markers of inflammation. Results: No significant histologic differences were identified between the cohorts, except there were more capsules with synovial metaplasia in the non-BII cohort. There was no statistical difference in thyroid-stimulating hormone, vitamin D levels, or complete blood count with differential between the cohorts. Next-generation sequencing revealed no statistically significant difference in positivity between Cohort A and B. Of the 12 cytokines measured, 3 cytokines, interleukin (IL)-17A, IL-13, and IL-22, were found to be significantly more often elevated in sera of subjects in Cohort A than in Cohorts B or C. The enterotoxin data demonstrated an elevation in immunoglobulin G (IgG) anti– Staphylococcus aureus enterotoxin A in Cohort A. There was no correlation between the presence of IgE or IgG anti- Staphylococcal antibody and a positive next-generation sequencing result. Conclusions: This study adds to the current literature by demonstrating few identifiable biomedical markers to explain the systemic symptoms self-reported by patients with BII.